Sodium oleate induced rapid gelation of silk fibroin. Issue 10 (3rd July 2018) - Yang, Yuejiao; Chen, Jie; Bonani, Walter; Chen, Bin; Eccheli, Sabrina; Maniglio, Devid; Migliaresi, Claudio; Motta, Antonella
Abstract: Silk fibroin has acquired increasing interest in the last years for application in medicine and namely in tissue engineering. Several methods have been developed to process fibroin and for the fabrication of nets, sponges, films and gels. This paper deals with the fabrication and characterization of fibroin hydrogels obtained by using sodium oleate as gelation agent. Gels have been prepared by mixing Silk fibroin (SF) and Sodium oleate (SO) water solutions in different concentrations, and a quite wide frame of compositions have been explored. Rheological tests have been performed to determine the gelation times, scanning electron microscopies have been made to evaluate morphologies, FTIR analysis has been done to determine the conformation of the starting materials and of the resulting gels, water content has been measured and cytotoxicity tests have been performed to validate the potential biomedical use of the hydrogels. Depending on the SF and SO different gelation times have been obtained thanks to the formation of intermolecular bonds between the fibroin chains. The obtained fastest gelation of about 80 s could make this specific formulation compatible with in situ gelation. By changing composition, gels with different morphologies, rheological properties and water contents have been prepared.